Unfolding the ramifications of workplace bullying: An empirical justification of conservation of resource theory in telecommunication sector of Pakistan - Muhammad Shaukat Malik; Shahzadi Sattar (Cogent Business & Management, 2022)
The current study is an attempt to explore the repercussions of workplace bullying in the telecommunication sector of Pakistan. To be precise, it assesses the influence of workplace bullying on emotional exhaustion resulting in the deterioration of employee performance. Drawing on Conservation of Resource Theory (COR), researchers tested the impacts of workplace bullying and cynicism on employee job performance where emotional exhaustion is the mediator between workplace bullying and employee performance. This study highlights the problematic confrontation by the telecom employees and suggests remedial actions to overcome this. The data is collected from 387 respondents of four telecommunications companies' franchises of southern Punjab Pakistan through a questionnaire-based survey. Purposive sampling is used in order to collect data from respondents encompassing managers and span of control. The data is analyzed using descriptive statistics and SMART-PLS using a bootstrapped moderated mediation method. The findings indicate a significant negative relationship between workplace bullying and employee performance. However, workplace bullying has a significant positive correlation with employees' emotional exhaustion, and when organizational cynicism as a moderator has been introduced, this relationship gets aggravated. The study results focus on the depletion of the psychological resources of employees by workplace bullying and organizational cynicism resulting in poor employee performance. Since employees may lose the psychological resources to cope with the situation, this issue must be addressed to replenish the psychological resources. Hence managers must introduce workplace bullying combating strategies to avoid harmful consequences.
Keywords: 650; affective event theory; emotional exhaustion; job performance; organizational cynicism; Workplace bullying